Happiness, debt & depression Is there a relationship between debt and depression in South Africa? - Sklair, Nathan (School of Economics, 2020)
While poor financial circumstances have been associated with an increased likelihood of depression, the role of personal debt in determining individual mental health is not fully understood. This paper investigates the existence of a causal relationship between individual debt and depression across 5 waves of panel data from the National Income Dynamics Study (NIDS). This paper adds to the existing literature on the relationship between consumer debt and mental health. The paper (i) explores the causal relationship between debt and mental health, (ii) conducts research between debt and mental health in a non-western economy, and (iii) considers the effect of various categories of debt on mental health e.g. mortgage debt, student debt, formal debt and informal debt. By using logistic fixed effects analysis, and exploiting the panel, the analysis controls for unobserved heterogeneity in the causal relationship between debt and depression. The paper finds that (I) Individuals who acquire informal debt in the current period have an increase in the odds of being depressed in both the current and future period. On the other hand, individuals who exhibit evidence of depressive symptoms in the current period have an increase in the odds of acquiring debt in the current period – but past period depressive symptoms do not appear to predict future period informal debt. Therefore, informal debt appears to exhibit characteristics of a bi-directional causal relationship in the current period, with informal debt associated with long term depressive symptoms. (II) Individuals with secure or mortgage debt exhibit a decrease in the odds of being depressed in the future, and (III) There is evidence that an individual who aquires formal debt and already depressed in the current period has a decrease in the odds of exhibiting symptoms of depression in the future period. This means that for unproductive debt categories debt appears to exhibit a negative effect on mental health and thus a decrease in lifetime utility. However, for productive debt categories such as secure debt, there is a positive effect on future mental health which may be argued to be an improvement in lifetime utility.